(untitled) (The Review of Diabetic Studies, 2025)
Emergency care environments are characterized by high patient acuity, time pressure, and complex clinical decision-making, where nursing interventions play a critical role in determining patient safety and health outcomes. This comprehensive review examines the impact of nursing interventions in emergency care settings, with a specific focus on clinical decision-making, patient safety, and outcome improvement. Drawing on evidence from peer-reviewed literature published between 2015 and 2025, the review synthesizes findings related to nursing-led triage, rapid patient assessment, early clinical interventions, continuous monitoring, and interprofessional communication in emergency departments. The evidence indicates that timely and well-coordinated nursing interventions significantly enhance the accuracy of clinical decisions, reduce adverse events such as medication errors and clinical deterioration, and improve key outcomes including mortality rates, length of stay, and patient satisfaction. Furthermore, the review highlights the importance of organizational support, workforce preparedness, and digital tools—such as electronic health records and clinical decision support systems—in enabling effective emergency nursing practice. Overall, the findings underscore that emergency nursing interventions are a cornerstone of high-quality emergency care and a critical driver of patient safety and outcome improvement.